Determination of o-phenylphenol and p-phenylphenol in aqueous samples using magnetic nanoparticles modified with cetyltrimethylammonium bromide by HPLC-FLD. Issue 13 (12th June 2015) - Wei, Han; Hang, Yiping; Zhu, Yudan; Song, Chenglong
Abstract : An obvious advantage of the method developed here is that magnetic adsorbents can be readily isolated from sample solutions with a magnet. Abstract : A simple magnetic solid-phase extraction method for the pre-concentration and determination of o -phenylphenol (OPP) and p -phenylphenol (PPP) using magnetic iron oxide nanoparticles (MIONPs) modified with cetyltrimethylammonium bromide (CTAB) has been developed. The MIONPs were analyzed by X-ray diffraction (XRD), transmission electron microscopy (TEM) and Fourier transform-infrared spectrometry (FT-IR). The influencing factors relevant to the solid-phase extraction such as pH, amount of sorbent, extraction time, sample volume, ionic strength and elution conditions were investigated and optimized. The developed method showed good linearity in the concentration range of 1–1000 μg L −1 ( R 2 ≧ 0.9996) and the relative standard deviation (RSD) was less than 10.6% ( n = 7) for the target analytes. The limit of detection (signal to noise ratio of 3) obtained for OPP and PPP were 0.1 and 1 μg L −1, respectively. The enrichment factors of OPP and PPP were 50 and 48.5, respectively. The results showed that the proposed method is a simple, rapid and low-cost technique for the pre-concentration and determination of OPP and PPP in aqueous samples.